Adjustable luminescence properties of Eu3+ and Bi3+ codoped Ca3Zn3Te2O12 phosphor. (August 2022) - Cao, Renping; Huang, Zhiyi; Lan, Bang; Li, Lan; Yi, Xuehua; Luo, Zhiyang; Liao, Chenxing; Wang, Jing
Highlights: Ca3 Zn3 Te2 O12 :Bi 3+, Ca3 Zn3 Te2 O12 :Eu 3+, Ca3 Zn3 Te2 O12 :Eu 3+ /Bi 3+ are prepared successfully in air. The green emission of Ca3 Zn3 Te2 O12 :Bi 3+ phosphor with excitation at 314 nm is observed. Under excitation at 395 nm, the red emission of Ca3 Zn3 Te2 O12 :Eu 3+ is observed. The adjustable color light of Ca3 Zn3 Te2 O12 :Eu 3+, Bi 3+ phosphor with excitation at 314 nm is revealed. Abstract: Ca3 Zn3 Te2 O12 :Bi 3+, Ca3 Zn3 Te2 O12 :Eu 3+, Ca3 Zn3 Te2 O12 :Eu 3+ /Bi 3+ are prepared successfully in air. The crystal phase, microscopic image, and optical properties of samples are investigated by the X-ray difractometer, scanning electron microscopy, and edinburgh steady-state FLS 980 spectrograph. The green emission of Ca3 Zn3 Te2 O12 :Bi 3+ phosphor with excitation at 314 nm is observed and its broad emission spectrum in the range of 360 - 790 nm is attributed to the 3 P 1  →  1 S 0 transition of Bi 3+ ion. Under excitation at 395 nm, the red emission of Ca3 Zn3 Te2 O12 :Eu 3+ is found, the chromaticity coordinates are (0.6392, 0.3605), and its PL spectrum is in the rang of 575 - 750 nm because of the 5 D 0  →  7 F 0, 7 F 1, 7 F 2, 7 F 3, and 7 F 4 transations of Eu 3+ ion. The doping Bi 3+ ion can affect the luminescence properties of Ca3 Zn3 Te2 O12 :Eu 3+ phosphor. The adjustable color light from green to yellow of Ca3 Zn3 Te2 O12 :Eu 3+, Bi 3+ phosphor with excitation at 314 nm is revealed when Eu 3+ concentration is changed from 0 to 12 mol%. When the excitation wavelength is 395 nm, Ca3 Zn3 Te2 O12 :Eu 3+, Bi 3+ phosphor only emits red light with emission spectrum in the rang of 575 - 750 nm. The energy level diagrams of Eu 3+ and Bi 3+ in Ca3 Zn3 Te2 O12 :Eu 3+, Bi 3+ are drawn, which is used to analyze the luminous mechanism of samples. Graphical abstract: Image, graphical abstract